THE COMPARISON OF USING NUMBERED HEAD TOGETHER (NHT) TECHNIQUES AND COOPERATIVE INTEGRATED READING COMPOSITION (CIRC) TECHNIQUES TOWARD READING COMPREHENSION - Fenny Thresia (Relawan Jurnal Indonesia, 2016)
Reading comprehension is a key point for basic English. The aim of this study is to find out the suitable technique between NHT and CIRC techniques in teaching reading. The design of this research was experimental design with pre-test and post-test design. The research was conducted at the Class Management. The number of population was 160 students, therefore, cluster random sampling was used as technique sampling. The students in each of experimental and control groups consisted of 32 students that classified from heterogenic students level. The result of the average score in experimental group was 63.40 and control group was 57.84. It meant that the result of reading scores in experimental group was higher than in control group. In other words, NHT technique was more effective than CIRC technique toward students reading comprehension in descriptive text